ISDN Applications in Education and Training - Mason, Robin 1967- (IET, 1994)
ISDN presents a new challenge for educators and trainers. This book provides an introduction to the technology for educators interested firstly in whether to use it and secondly in how to use it. The first three chapters discuss practical, educational and strategic issues related to these two questions. The following ten chapters provide case studies of education and training uses of ISDN technologies in Europe, the US and Australia. These involve videoconferencing, audiographics, desktop conferencing and image banks. The book concludes with a large glossary of explanatory material
Keywords: Education; Integrated services digital networks; Training; education; ISDN; training